2017
DOI: 10.1002/cbdv.201600421
|View full text |Cite
|
Sign up to set email alerts
|

Two New Ergosterol Derivatives from the Basidiomycete Cortinarius glaucopus

Abstract: Two new sterols 1 and 2 and five known ones 3 - 7 were isolated for the first time from the fruiting bodies of Cortinarius glaucopus. Their structures were established by 1- and 2D-NMR spectra and HR-FABS-MS. The relative configuration of 1 was firmly determined by comparison of the observed H- H couplings and NOESY correlations, with those predicted for the computed geometries of the conformers. Calculations were performed by means of DFT with the B3LYP functional at 6-31 + G(d,p) level of theory, in CHCl as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Comparison of the NMR data made it possible to assign the structure of 199 as the C-22 isomer of strophasterol A that was later confirmed by X-ray analysis [ 193 ]. Structure of strophasterol C ( 200 ) was proposed based on NOE correlations by Aung et al, who isolated it from the basidiomycete Cortinarius glaucopus together with glaucoposterol A ( 203 ) [ 195 ]. Additional evidence for the structure of 200 was obtained by its chemical synthesis [ 308 ].…”
Section: Ergostanes With a Rearranged Tetracyclic Skeletonmentioning
confidence: 99%
“…Comparison of the NMR data made it possible to assign the structure of 199 as the C-22 isomer of strophasterol A that was later confirmed by X-ray analysis [ 193 ]. Structure of strophasterol C ( 200 ) was proposed based on NOE correlations by Aung et al, who isolated it from the basidiomycete Cortinarius glaucopus together with glaucoposterol A ( 203 ) [ 195 ]. Additional evidence for the structure of 200 was obtained by its chemical synthesis [ 308 ].…”
Section: Ergostanes With a Rearranged Tetracyclic Skeletonmentioning
confidence: 99%
“…The structures of strophasterols A and B, including their absolute configurations, were determined to be 1 and 2 , respectively, by X‐ray crystallographic analysis of the corresponding bis‐ p ‐bromobenzoates (Figure ), while strophasterols C and D were only given a planar structure represented by 3 that bears an additional keto functionality at the C23 position . Quite recently, Aung and co‐workers also isolated strophasterol C from the fruiting body of Cortinarius glaucopus , along with some novel steroids, including glaucoposterol A ( 4 ), with the same carbon skeleton as the strophasterols, and they revealed the absolute configuration of strophasterol C to be the same as that of strophasterol A based mainly on its NOESY spectrum and biosynthetic considerations . The totally unprecedented carbon framework found in strophasterols A–D and glaucoposterol A was hypothesized to be biosynthesized from ergosterol ( 5 ) via 6 , a suppressor of osteoclast formation also isolated from S. rugosoannulata , through D‐ring cleavage followed by bond formation between C15 and C22 to form a new five‐membered ring (ring D′; see structure 1 ) characteristic of this small family of natural products .…”
Section: Figurementioning
confidence: 99%
“…Strophasterols A–F ( 1–6 , respectively) and glaucoposterol A ( 7 ) are secondary metabolites from mushrooms that share a recently discovered 15(14→22) abeo -ergostane skeleton (Figure ). These compounds are considered to be biosynthesized from ergosterol ( 8 ) via cleavage of the C14–C15 bond in the D-ring followed by formation of a bond between the resulting C15 terminus and the C22 position on the side chain to form an isolated cyclopentane ring (D′-ring) characteristic of this class of natural products. , The first report of the isolation of abeo -steroids of this structural type was published by Kawagishi and co-workers in 2012 . They isolated strophasterols A–D ( 1–4 , respectively) from the edible mushroom Stropharia rugosoannulata and revealed that strophasterol A ( 1 ) has anti-MRSA and neuronal cell-protecting activities .…”
mentioning
confidence: 99%
“…The structures of 1 and 2 , including their absolute configurations, were determined unambiguously by X-ray crystallographic analysis of the corresponding bis­( p -bromo)­benzoates, while the stereochemistries of strophasterols C ( 3 ) and D ( 4 ) were left unassigned. Aung and co-workers also isolated strophasterol C ( 3 ) along with a new member of this family [glaucoposterol A ( 7 )] from the fruiting bodies of Cortinarius glaucopus and proposed the new skeletal name “strophastane” for the abeo -steroidal carbon framework common to 1–7 . The absolute configuration of 3 was assigned on the basis of re-examination of its NMR data, including NOESY correlations and biosynthetic considerations, while that of 7 was proposed mainly on the basis of its NOESY experiments coupled with DFT calculations.…”
mentioning
confidence: 99%